(untitled) (Journal of Social Sciences Review, 2025)
This study aims to investigate the effect of e-WOM on consumers’ purchase intention for green eco-label products in the context of environmental sustainability and to explore how to create positive e-WOM by using these determinants. A structured questionnaire was used to collect the data from 400 graduate and postgraduate students who had knowledge of green eco-label products. The data were analyzed through structural equation modeling (SEM). Results indicate that homophily, tie strength, valence of comments, receiver’s search extent and perceived source credibility have significant relationship with green purchase intention. Likewise, electronic review adoption and green purchase intention also have a positive relationship. The research results provide marketers with an understanding of young consumers’ intention regarding the purchase of green eco-label products, which ultimately supports the purchase intention of buying green products From a managerial standpoint, this study provides valuable insights into how marketers can tap into key factors of electronic word-of-mouth (e-WOM) to sway consumer behavior towards sustainable choices. Businesses can strategically increase consumer engagement with green products by creating online spaces that prioritize reliable sources, pertinent peer networks, and positive message framing. The research introduces a detailed model of e-WOM factors that can guide focused digital marketing strategies, with the goal of enhancing green brand visibility and encouraging environmentally conscious consumer.